(untitled) (Iranian Journal of Kidney Diseases, 2009)
Introduction. We compared the effect of higher and lower doses of folic acid compared to our routine daily dose on plasma homocysteine levels, in our hemodialysis patients. Materials and Methods. Eighty patients on hemodialysis receiving oral folic acid, 10 mg/d, were randomized to receive folic acid at either doses of 5 mg/d (group 1) or 15 mg/d (group 2) for 2 months. Plasma levels of total homocysteine were measured before and after the study period. Results. Hyperhomocysteinemia was seen in 75 patients (93.8%) before, and in 37 patients of group 1 (92.5%) and 39 of group 2 (97.5%) after the study period. In group 1, a nonsignificant decrease occurred in plasma homocysteine level (29.67 ± 12.26 ?mol/L to 27.78 ± 9.94 ?mol/L, P = .30), while in group 2, there was a significant decrease in homocysteine level (32.40 ± 9.76 ?mol/L to 29.58 ± 9.62 ?mol/L, P = .01). Changes in homocysteine level correlated with its baseline level (r = -0.42, P < .001). In both groups, significant reductions in homocysteine level were seen mostly in those patients with high baseline homocysteines. Conclusions. Routine folic acid supplementation of 10 mg/d could not normalize plasma homocysteine levels in most of our patients. Increasing folic acid dose made a statistically significant but clinically trivial decrease in homocysteine levels, and could not normalize homocysteine level in most patients. Patients with a higher baseline homocysteine level achieved a greater reduction, which may be explained by primary noncompliance of some patient. Further investigation of folic acid dosage is suggested.